2014
DOI: 10.5539/sar.v3n4p75
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Number and Rate of Goat Manure Application on Soil Properties, Growth and Yield of Sweet Maize (Zea mays L. saccharata Strut)

Abstract: Alternative sources of plant nutrients have now become highly imperative especially for vegetable crop production in Nigeria. Due to the escalating costs, environmental and health problems associated with excessive use of inorganic fertilizers on continuously cropped fields, there is a need for more research on the use of organic manures and residues. A field experiment was conducted in the late growing season from September to December, 2012 in Calabar, a humid forest agroecology in south eastern Nigeria to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 10 publications
7
27
0
2
Order By: Relevance
“…This might have been attributed to the chemical composition of the manures. This observation corroborated the findings by Uwah et al (2014) who reported that both poultry and goat manures improved chemical properties of the soil and enhanced the agronomic performance of sweet maize. Sweet corn leaf chlorophyll content was found to be higher under poultry and goat manures in this study.…”
Section: Effect Of Animal Manure Npk and Soil Type On Leaf Areasupporting
confidence: 91%
“…This might have been attributed to the chemical composition of the manures. This observation corroborated the findings by Uwah et al (2014) who reported that both poultry and goat manures improved chemical properties of the soil and enhanced the agronomic performance of sweet maize. Sweet corn leaf chlorophyll content was found to be higher under poultry and goat manures in this study.…”
Section: Effect Of Animal Manure Npk and Soil Type On Leaf Areasupporting
confidence: 91%
“…The oobservations were including plant length (cm), leaf lenght (cm), number of leaves, number of dead leaves, number of suckers, leaf maturation age (days) and tillers emerged age (week), which was observed in 4,6,8,10,12,14, and 16 WAP. Data of the Salak were recorded and subjected to one-way analysis of variance (ANOVA) at the significant level of 5%.…”
Section: Methodsmentioning
confidence: 99%
“…Manure addition as backfill on the planting-hole intended to nourish the rooting space, so it can be easier to be absorbed by roots. [6] stated that organic fertilizers can improve soil structure, increase water absorption, increase the quantity of soil microorganism, and source of nutrients for plants. [7] stated that the function of goat manure were able to develop some nutrients such as phosphorus, nitrogen, sulfur, cations and release P element from oxidation of Fe on soil and forming a complex compound with macro and micro elements, so the plant can reduce the leaching of the element contains.…”
Section: Introductionmentioning
confidence: 99%
“…The use of organic fertilizer aims to improve the physical, biological and chemical properties of soil to grow roots quickly and freely move in the soil (Rahim, 2000). Uwah and Eyo (2014) also stated that the provision of manure gives a significant effect on maize in parameter plant height, number of leaves and stem diameter. The response is related to the nutrient content of manure hat can increase the soil absorption of the soil to water and helps the nutrient uptake of chemical fertilizers provided.…”
Section: Introductionmentioning
confidence: 99%